Competition between Tropomyosin, Fimbrin, and ADF/Cofilin drives their sorting to distinct actin filament networks - Jenna R Christensen (eLife, 2017)
The fission yeast actin cytoskeleton is an ideal, simplified system to investigate fundamental mechanisms behind cellular self-organization. By focusing on the stabilizing protein tropomyosin Cdc8, bundling protein fimbrin Fim1, and severing protein coffin Adf1, we examined how their pairwise and collective interactions with actin filaments regulate their activity and segregation to functionally diverse F-actin networks. Utilizing multi-color TIRF microscopy of in vitro reconstituted F-actin networks, we observed and characterized two distinct Cdc8 cables loading and spreading cooperatively on individual actin filaments. Furthermore, Cdc8, Fim1, and Adf1 all compete for association with F-actin by different mechanisms, and their cooperative association with actin filaments affects their ability to compete. Finally, competition between Fim1 and Adf1 for F-actin synergizes their activities, promoting rapid displacement of Cdc8 from a dense F-actin network. Our findings reveal that competitive and cooperative interactions between actin binding proteins help define their associations with different F-actin networks.